HUBUNGAN ANTARA UMUR DAN PARITAS IBU DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PAKJO PALEMBANG TAHUN 2010 - Tiara Fatrin; Dina Oktariani (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
The number of mother death (AKI) is one of the main indicator in health service in a country. The maternal death can be caused by some factors, one of them is anemia case. In Indonesia the anemia prevalention of pregnancy was still high around 40,1 % (SKRT, 2001), Lautan J dkk (2001) reported that from 31 pregnant women on trimester II there were 23 (74 %) with anemia, and 13 (42 %) with low energy to the pregnant mother and partus, so that this problems need to be solved. The causing factors related to the anemia of pregnant mother were mother age < 20, ANC, birth rate, parity, and mother compliance toward the anemia case.The objective of this research was to find out the correlation between age and mother parity to the anemia case in Pakjo public health centre Palembang 2010. the methods of this research was analytic survey through Cross Sectional, and the analysis tools by using check list. The population of this research was all the pregnant mother who investigating their pregnancy health in Pakjo public health centre Palembang on January-May 2010. The technique in collecting the samples systematic random. Through data analysis chi-square statistic test through computerization found that there were significant correlation between mother age to the anemia case where P.Value = 0,005 less than α = 0,05 and also there were significant correlation between mother parity to the anemia case where P.Value = 0,038 less than α = 0,05. The conclusion of this research, state that there were significant correlation between mother age to the anemia case of pregnant mother and also there were significant correlation between mother parity to the anemia case.